The future low-carbon value chain framework in selected Philippine industries using scenario building - De Villa, Yoshiko Zoe
This project paper is concerned on the assessment of the future supply chain model of the automotive, healthcare, and food production industries as the global economy, including the Philippines, transitions to a low-carbon. Furthermore, a quick assessment on the sources of emissions and how the value chain activities can adopt to the transition has been conducted. The scenario building process was the tool used in this project paper.